Histomoníase em peru (Meleagris gallopavo): relato de caso - Silva, Tarcísio Macedo [UNESP]; Okamoto, Adriano Sakai [UNESP]; Smaniotto, Bruna Domeneghetti [UNESP]; Paes, Antonio Carlos [UNESP]; Andreatti Filho, Raphael Lucio [UNESP] (My University, 2014)
The histomoniasis or blackhead caused by Histomonas meleagridis, can produce an enterohepatite in birds. In general, the turkeys (Meleagris gallopavo) are more susceptible; however, birds on twelve weeks have higher mortality rates. Transmission occurs by ingestion of nematode Heterakis gallinarum or their embryonated eggs. Contact with contaminated feces by H. meleagridis and ingestion of worms contaminated with nematode are also sources of transmission of the disease. The aim of the work was to report the occurrence of histomoniasis in a young turkey attended at the ornitopathology laboratory at school veterinary hospital – Paulista State University (FMVZ – UNESP) Sao Paulo, Botucatu campus. Brazil.

La histomoniasis o cabeza negra, causada por la Histomonas meleagridis, ocasiona un cuadro de enterohepatitis en las aves que afecta. De las aves en general, los pavos (Meleagridis gallopavo) de todas las edades son los más suceptíbles, sin embargo, la mortalidad es más elevada en aquellos con aproximadamente 12 semanas de vida. La transmisión se produce por la ingestión de nematodeos Heterakis gallinarum o sus huevos embrionados. Póngase en contacto con heces contaminadas de H. meleagridis y la ingestión con gusanos nematodeos contaminados también son fuentes de transmisión de la enfermedad. El presente artículo tuvo como objetivo relatar un caso de histomoniasis en un pavo joven atendido en el laboratorio de Ornitopatología del Hospital Veterinario de la Facultad de Medicina Veterinaria y Zootecnia de la Universidad Estadual Paulista (FMVZ-UNESP), campus de Botucatu-SP. Brasil.

A histomoníase ou cabeça negra, causada pelo Histomonas meleagridis, ocasiona um quadro de enterohepatite nas aves acometidas. Das aves em geral, os perus (Meleagridis gallopavo) de todas as idades são os mais suscetíveis, porém, a mortalidade é mais elevada naqueles com aproximadamente 12 semanas de vida. A transmissão ocorre pela ingestão do nematóide Heterakis gallinarum ou seus ovos embrionados. O contato com fezes contaminadas pelo H. meleagridis e ingestão de minhocas contaminadas com o nematoide também são fontes de transmissão da enfermidade. O presente relato teve como objetivo apresentar um caso de histomoníase em um peru jovem atendido no laboratório de Ornitopatologia do Hospital Veterinário da Faculdade de Medicina Veterinária e Zootecnia da Universidade Estadual Paulista (FMVZ – UNESP), campus Botucatu – SP. Brasil.
Histomoniasis in turkey (Meleagris gallopavo): a case report
Histomoniasis en pavos (Meleagris gallopavo): relato del caso
Keywords: Enterohepatite; Histomoniasis; Histomonas melleagridis; Meleagris gallopavo; Turkeys; Enterohepatitis; Histomoniasis; Histomonas melleagridis; Meleagris gallopavo; Pavos; Enterohepatite; Histomoníase; Histomonas melleagridis; Meleagris gallopavo; Perus